(untitled) (Revista de Ciências Agroveterinárias, 2019)
The aim of this study was to evaluate the intra-plant distribution of Crysodeixis includens in conventional FM 993 and transgenic FM 975 WS (WideStrike), which express the toxic proteins Cry1Ac and Cry1F. The experiment was carried out in a split-plot design arranged under a complete block design with six treatments (three thirds x two plant leaf surface) and 40 repetitions. The plants were visually divided into three thirds (upper, middle and lower) and into adaxial and abaxial leaves, registering the number of caterpillars. C includens caterpillars were found at higher numbers in the non-Bt cultivar (FM 993), while in the transgenic cultivar FM 975 WS (WideStrike) were found only small caterpillars, and significantly fewer compared to their non-Bt isoline (FM 993). Caterpillars, regardless of size and cultivar, were most commonly found at the bottom and middle thirds of the plant canopy and on the abaxial leaf surface.